PENGARUH BANTUAN PRODUKTIF USAHA MIKRO (BPUM) TERHADAP PENDAPATAN UMKM (Studi Pada UMKM di Desa Kerato Kecamatan Unter Iwes) - Abdul Rahim; Elly Karmeli; Susi Paramita (Jurnal Ekonomi & Bisnis, 2021)
This study aims to know the effect of micro enterprise productive aid (BPUM) toward the income of traders in Kerato Village, Unter Iwes Sub-district, Sumbawa District. The method used in this study was associativ. The data used in this study were primary and secondary data. The primary data in this study were answers that have obtained from interviews with the actors of Micro, Small and Medium Enterprises (UMKM) that have received micro-enterprise productive aid (BPUM) and secondary data in this study obtained from Cooperative and Small and Medium Industrial and Trade Office of Sumbawa (Diskoperindag) especially in UMKM sector. Data collection methods used in this study were documentation and interviews. The analytical tool used was the t-statistic test. The results of study showed that based on data analysis, data interpretation and results of the simple linear regression test showed that there was effect of micro enterprise productive aid (BPUM) toward traders’ income, it was based on the result of t-value of 5.466 was higher than the value of t-table of 1.674. Based it result it means that HO was rejected because t-value was higher than t-table (5.466>1.674).